Energy Audits and Energy Efficiency in Small Wastewater Treatment Plants: A Case Study - Cardoso, Bruno J. (2019)
Energy plays an important role in the water sector. In fact, energy consumption by this sector accounts for nearly 44% of municipalities’ energy costs in developed countries. To minimize adverse environmental and human health impacts wastewater can undergo three treatment levels before discharge or reuse. Since it is an energy intensive process, wastewater treatment represents the largest share of water-related electricity consumption in developed countries. According to the literature, there is a potential for improvement and energy savings in wastewater treatment facilities. Indeed, International Energy Agency states that, the energy consumption in the water sector can be reduced by 15% if this potential is harnessed. Consequently, energy audits can provide valuable information about those facilities, allowing to assess their energy performance and to identify energy-saving opportunities. In this paper the results of internal energy audits conducted in two “small” wastewater treatment plants, located in the North of Portugal, are presented and analyzed. The results, 13% and 22% savings, show that simple energy audits, which can be implemented by company members, should not be considered as a cost, but rather as a step to a more efficient energy use, reducing energy costs and environmental impacts.